When Group Memberships are Negative: The Concept, Measurement, and Behavioral Implications of Psychological Disidentification - Becker, Julia C.; Tausch, Nicole (Self and identity, 2014)
This research introduces a multi-component model of ingroup disidentification that distinguishes three disidentification components (detachment, dissatisfaction, and dissimilarity). In Studies 1a (N = 168) and 1b (N = 215), the authors developed a measurement scale that assesses these components, and examined alternative factorial structures. Study 2 (N = 115) provides evidence that the disidentification scale performs better at distinguishing between disidentification and nonidentification than an established identification scale. Using additional data from Studies 1b and 2, Studies 3a and 3b examined emotions and behavioral intentions as correlates of disidentification and revealed that the disidentification components predict negative ingroup-directed behavioral intentions (active harm, passive harm, and passive facilitation) and identity concealment over and above measures of identification. Theoretical implications for research on social stigma and social change are discussed.